Tracing tetraether lipids from source to sink in the Rhône River system (NW Mediterranean) - Kim, Jung-Hyun; Ludwig, Wolfgang; Buscail, Roselyne; Dorhout, Denise; Sinninghe Damsté, Jaap S. (Frontiers in Earth Science, 2015)
In this study, we investigated soils and river suspended particulate matter (SPM) collected in the Rhône and its tributary basins as well as marine surface sediments taken in the Rhône prodelta (Gulf of Lions, NW Mediterranean). Thereby, we traced the signal of branched glycerol dialkyl glycerol tetraethers (brGDGTs) from the source to sink via the Rhône River and its tributaries and identified sources of brGDGTs in rivers and marine sediments. Soil pH rather than the mean annual air temperature (MAAT) explains most of the observed variances of the brGDGT distribution in our soil dataset. The observed changes in the distribution of brGDGTs in the river SPM indicate that brGDGTs brought by the river to the sea are primarily derived from the lower Rhône and its tributary soils, even though in situ production in the river itself cannot be excluded. In marine surface sediments, it appears that the input of riverine brGDGTs is the primary source of brGDGTs in the Rhône prodelta, although the brGDGT composition may be further modified by the in situ production in the marine environment. More work is required to assess fully whether brGDGTs can be used to reconstruct the terrestrial paleoenvironmental changes using marine sediment cores taken in the Rhône prodelta close to the river mouth.